Optimizing IVF outcomes for women with diminished oocyte reserve. (September 2013) - Check, Jerome H
Women with diminished oocyte reserve do not have very poor oocyte quality similar to women of advanced reproductive age. The very poor pregnancy rates found in many studies of IVF-ET in this population seems to be related to the use of high-dosage FSH stimulation. The presence of significant elevated FSH levels leave many women more prone to FSH receptor downregulation. The best 'hypothesis' to fit the poor success rate found with high FSH stimulation is that FSH receptor downregulation leads to an insufficient production of a factor needed to prevent non-disjunction of chromosomes, leading to the creation of embryos with a high percentage of aneuploidy. Mild stimulation, to a reasonable degree obviates the problem with FSH receptors and results in the production of live healthy babies.